Effect of hot air drying on the protein content of Nostoc Sphaericum - Rodriguez Yupanqui, Christian Joel; Castillo Leon, Luis Anthony Steban; Pelaez Alfaro, Johan Lenis; Silva-Chuquipoma, Diego Honorato; Boñón Silva, Cesia Elizabeth (LACCEI, 2024)
This study aimed to evaluate the effects of hot air drying on the protein content of dehydrated Nostoc sphaericum. A population of 5 kg of Nostoc was used, divided into two treatments: Treatment 1 (T1) with 2 kg dried at 70 °C for 8 hours, and Treatment 2 (T2) with 3 kg dried at 90 °C for 5 hours. After the drying process, the dehydrated samples were analyzed to determine their protein content using the Kjeldahl method. The results showed that T2 achieved a higher protein content (34.15%) compared to T1 (30.75%). However, a t-student t-test with a 95% significance level revealed that these differences were not statistically significant (p-value of 0.328). In conclusion, hot air drying is an effective method for dehydrating Nostoc, maintaining protein integrity despite differences in drying conditions, suggesting its viability for future applications in the food and pharmaceutical industries.